(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article provides a semantic and contrastive analysis of blessing and curse phrases in the English and Uzbek languages. Blessings and curses represent two opposite types of evaluative expressions that convey positive and negative wishes respectively. The study examines their semantic structure, functional features, connotative meanings, and linguocultural specificity. By comparing English and Uzbek data, the article identifies both universal semantic components and culture-specific characteristics that reflect national values, religious beliefs, and social norms.